Using virtual reality mediation in a workplace setting for employees with disabilities: A pilot study - Hung Jen Kuo; Nigel Newbutt; Sarah George; Michael Laird (Computers & Education: X Reality)
Virtual Reality (VR) evolves rapidly as a pervasive media and many have started to explore how VR can be used to support a wide range of people. VR technology is also being increasingly integrated into both business and educational settings, offering immersive experiences that enhance learning, training, collaboration, and customer engagement. More recently, the use of VR to aid employment for individuals with disabilities has become a topic of interest. One such innovation use case is the integration of VR meditation practices. VR meditation offers a promising avenue to enhance the well-being of individuals with disabilities in the workplace by providing an immersive method to manage stress, enhance focus, and foster relaxation. This pilot study included 23 participants with disabilities who engaged in daily 5-min VR meditation sessions for three days. Results demonstrated the feasibility and preliminary efficacy of the intervention. Participants reported positive experiences, including increased job satisfaction, work engagement, quality of life, and mindfulness. Statistically significant improvements were observed in participants’ work engagement. Participants also provide suggestions for employers looking to adopt a similar approach.